Helping Children Become the Heroes of their Stories : a practical guide to overcoming adversity and building resilience in every setting - Seyderhelm, Amanda (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Whether it's the anxiety of social isolation, the loss of routine, or a breakdown in formal educational support, the COVID pandemic has affected children in countless ways. Teachers, therapists and parents frequently find themselves ill-equipped to help children struggling with the difficult feelings that these situations, and others like them, bring. This essential guide provides a therapeutic toolkit to enable children to tell their stories and to regain some control over their mental health and wellbeing. The toolkit introduces a therapeutic story template, alongside guided support and examples focusing on three therapeutic skill sets: active listening, reflection and handling questions. Designed for use with children both individually and in class groups, the storytelling toolkit will enable children to see themselves as the hero of their own story, and life, and to reinstate a sense of optimism and self-empowerment in the face of the pandemic challenge. This resource provides a practical toolkit which can be used both inside and outside the classroom to help children to tell their lockdown stories. It will be valuable reading for teachers, SENCOs, therapists, mental health leads and parents"--
In preparation -- The skills -- The space -- The call -- Refusal of the call -- Meeting the mentor -- Crossing the first threshold -- Finding allies and enemies -- Revelation -- Celebration -- Setting up a Hero's journey storytelling group -- When to seek further support.
Includes bibliographical references and index.
Keywords: Narrative therapy; Resilience (Personality trait) in children; Child psychotherapy -- Methodology